2023
DOI: 10.3390/app13042418
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of Fracture Behavior for Transversely Isotropic Slate Using Semi-Circular Bend Method

Abstract: Slate with inherently transverse isotropy is abundant in metamorphic rock, in buildings, and in geotechnical engineering worldwide; the tensile and shear fracture behavior of layered slate is vital to know for engineering applications. In this paper, the Brazilian and semi-circular bend (SCB) tests of layered slate were performed. The fracture characteristics of the slate were investigated by numerical simulations developed by the hybrid finite and cohesive element method (FCEM). Results showed that the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The parameters included a load cell of 1 kN and a testing rate of 10 mm/s. From the forcedisplacement curve, the strain (ε), maximum stress at failure (σ), and Young's modulus were determined, according to Equations ( 5)- (7), where σ represents the supported stress in MPa, F is the applied force in N, A is the specimen's cross-sectional area in mm 2 , the strain (ε) is calculated by dividing the length increase (∆L) by the specimen's original length (L 0 in the calibrate length of 10 cm), E is the Young's modulus in MPa, ∆σ is the stress increase in MPa, and ∆ε is the dimensionless strain increment in the initial linear zone.…”
Section: Tensile Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters included a load cell of 1 kN and a testing rate of 10 mm/s. From the forcedisplacement curve, the strain (ε), maximum stress at failure (σ), and Young's modulus were determined, according to Equations ( 5)- (7), where σ represents the supported stress in MPa, F is the applied force in N, A is the specimen's cross-sectional area in mm 2 , the strain (ε) is calculated by dividing the length increase (∆L) by the specimen's original length (L 0 in the calibrate length of 10 cm), E is the Young's modulus in MPa, ∆σ is the stress increase in MPa, and ∆ε is the dimensionless strain increment in the initial linear zone.…”
Section: Tensile Testmentioning
confidence: 99%
“…The deformability and strength of slate rocks depend on the orientations of their planar structures relative to the applied stresses [2,3]. Extensive research has been conducted on the fracture of slate and its simulation, driven by the need to ensure its resilience in various structural or decorative applications [4][5][6][7][8]. In these studies, it has been consistently concluded that slate fractures invariably occur between the layers regardless of the direction of the external stresses.…”
Section: Introductionmentioning
confidence: 99%